LAGRANGIAN DUALITY FOR VECTOR OPTIMIZATION PROBLEMS WITH SET-VALUED MAPPINGS - Long, Xian-Jun; Peng, Jian-Wen (Taiwanese journal of mathematics, 2013)
In this paper, by using a alternative theorem, we establish Lagrangian conditions and duality results for set-valued vector optimization problems when the objective and constant are nearly cone-subconvexlike multifunctions in the sense of E-weak minimizer. 2010Mathematics Subject Classification: 90C29, 90C46. Key words and phrases: Set-valued vector optimization problems, Lagrangian duality, Alternative theorem, E-weak minimizer, Nearly cone-subconvexlikeness.